PERANCANGAN ULANG TATA LETAK FASILITAS DALAM MENINGKATKAN EFEKTIVITAS PRODUKSI (STUDI OBSERVASI PT. KALIMANTAN CONCRETE ENGGINERRING) - Rakhmat Fauzy; Qomariyatus Sholihah (JTAM ROTARY, 2019)
Industry is an economic activity that processes raw materials, raw materials, semi-finished goods or finished goods into high-quality goods in use, including engineering and engineering activities. Thus, industry is part of the production process. Industrial materials are taken directly or indirectly, then processed, resulting in more valuable goods for the community. In an industry not only concerns how much investment should be invested, production procedures and marketing of products but also requires the planning of facilities that include the location planning facility and facility design. Facility design includes facility system design, factory layout and material handling system (material transfer). (Wikipedia Bahasa Indonesia). In its current development PT. Kalimantan Concrete Engineering extends production land by purchasing a plot of land adjacent to the current production site, but it has not been enabled yet, in addition to the placement of U-dith and Box Culvert production which have not been placed in accordance with its area in the current name still in place at road front office and other areas that are still far apart. In accordance with the above explanation, we can know that the importance of an effective and efficient facility layout planning where it is in need in material handling arrangements, time efficiency, and the flow of work mobility. So this research is expected to be able to provide trobosan in the relationship layout facilities and improve the effectiveness of work better. Keywords: PT. Kalimantan Concrete Engineering, ARC, MHPS, Efektivitas